Pengaruh EPS, DPS, PBV, dan DER Terhadap Harga Saham(Closing Price) PT. Unilever Indonesia Tbk. Periode 2015-2022 - Fitrotus Solekah, Tutut Fitrotus Solekah; Erdkhadifa , Rendra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Fast Moving Consumer Goods companies are one of the sources in realizing investment with the main sources of daily necessities, such as food, beverages, household products, and beauty products. However, it turns out that recently the share price of PT. Unilever Indonesia actually experienced a very significant decline. This study aims to determine the effect of EPS, DPS, PBV and DER on stock prices. This study uses a quantitative approach. The data used in this study is secondary data taken from the financial statements of PT. Unilever Indonesia Tbk for the 2015-2022 period. The data analysis used is multiple linear regression analysis using review. The results showed that partially the EPS variables have no effect on stock prices. While the DPS, PBV and DER variables had a positive effect on stock prices. The simultaneous results show that the EPS, DPS, PBV and DER variables affect stock prices.